Implementation of the Principles of Legal Certainty and Accuracy in State Administrative Decisions within the Police Environment: Case Study of the Bengkulu Regional Police - Maya, Alvina; Zahara, Widya Rahmi; Al Mursalin, Muhammad Zakky; Wulandari, Wulandari (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study examines the implementation of the principles of legal certainty and due care in the issuance of State Administrative Decisions (Keputusan Tata Usaha Negara/KTUN) by the Bengkulu Regional Police. The case under review concerns the Decree of the Chief of Bengkulu Regional Police Number Kep/30/II/2025 regarding the Dishonorable Discharge (Pemberhentian Tidak Dengan Hormat/PTDH) of a police officer. The research employs a normative juridical method, utilizing statutory approaches, legal doctrines, and an analysis of decisions issued by the Bengkulu State Administrative Court (PTUN) as the primary data sources. The findings indicate that although the decision formally complied with procedural requirements, it materially violated the principles of legal certainty and due care. The authorized official failed to consider a reconciliation agreement, which under Police Regulation Number 7 of 2022 should have served as a basis for terminating the disciplinary examination. This omission resulted in an inaccurate legal basis and a decision that did not fully reflect the actual circumstances of the case. Furthermore, weaknesses in factual verification demonstrate a lack of prudence in the decision-making process. The reasoning of the Bengkulu State Administrative Court reinforces these findings, concluding that the disputed decision was inconsistent with the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB) as stipulated in Law Number 30 of 2014. This study recommends strengthening the application of AUPB through enhanced diligence, the improvement of internal standard operating procedures, and the optimization of factual verification mechanisms to ensure accountable and lawful administrative governance within the police institution.This study examines the implementation of the principles of legal certainty and due care in the issuance of State Administrative Decisions (Keputusan Tata Usaha Negara/KTUN) by the Bengkulu Regional Police. The case under review concerns the Decree of the Chief of Bengkulu Regional Police Number Kep/30/II/2025 regarding the Dishonorable Discharge (Pemberhentian Tidak Dengan Hormat/PTDH) of a police officer. The research employs a normative juridical method, utilizing statutory approaches, legal doctrines, and an analysis of decisions issued by the Bengkulu State Administrative Court (PTUN) as the primary data sources. The findings indicate that although the decision formally complied with procedural requirements, it materially violated the principles of legal certainty and due care. The authorized official failed to consider a reconciliation agreement, which under Police Regulation Number 7 of 2022 should have served as a basis for terminating the disciplinary examination. This omission resulted in an inaccurate legal basis and a decision that did not fully reflect the actual circumstances of the case. Furthermore, weaknesses in factual verification demonstrate a lack of prudence in the decision-making process. The reasoning of the Bengkulu State Administrative Court reinforces these findings, concluding that the disputed decision was inconsistent with the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB) as stipulated in Law Number 30 of 2014. This study recommends strengthening the application of AUPB through enhanced diligence, the improvement of internal standard operating procedures, and the optimization of factual verification mechanisms to ensure accountable and lawful administrative governance within the police institution.